The Evolution of an Online Geoscience Lab Course: Experiences from a Regional University - Depriest, Thomas Lan; Wilson, Adam; Mehlhorn, Joey (Journal of Education and Training, 2024)
This article seeks to provide a template for faculty to address the challenges of teaching an online lab science course and the efforts of faculty and staff to ensure quality, academic integrity, and student success by relating our university’s experience in developing and continuing to evolve our geoscience lab course for online delivery over twenty years. After a brief review of the literature surrounding the pedagogy and challenges of teaching online lab science course, the bulk of this article will address UT Martin’s path navigating from early iterations of general education Geology lab courses to the versions offered currently.